ORIGIN AND QUALITY OF THERMAL GROUNDWATERS IN THE REGION OF FARSALA (E. THESSALY/GREECE)
Farsala Basin presents a remarkable geothermal interest. Areas exhibiting geothermal potential are directly related to faulted zones, represented mainly by cross-faulted systems of E-W, NW-SE and NNE-SSW direction. Thermal waters occur in the areas of Ampelia and Krini in boreholes of 420 m depth. Their temperature ranges between 20,5° and 39,1° C. Thermal waters originate from meteoric waters, which have been infiltrated and heated in great depths, moved towards the surface through faults and hosted in the aquifers of coarse - grained formations find in the area. Their chemical composition is controlled by their contact with the volcanic parts (pillow lavas) of the ophiolithic series. They show alkaline character and low salts concentration. Waters of Ampelia region, which belong to Na-HCO^ type, exhibit temperatures from 27,9° to 39,1° C and low salt concentrations (405- 607 mg/l TDS). On the contrary, waters of Krini area present lower temperatures (20,5° -26,2° C) and higher salt concentrations (734-1850 mg/l TDS). These waters belong to Na-Mg-Ca-HCO^and Na-S04 -Cl-HCO